Juventude universitária nos anos 1980: as práticas culturais do movimento estudantil na UFRN - Maia, Michelle Pascoal (2009)
The 1980s, at UFRN represented a moment of resumption of student struggles. The major goals of the student movement in this period was the fight against the authoritarian regime and for the democracy within and outside the university. In this context, events, activities, artistic and cultural productions were organized in order to make a critical policy for the procedure, trying to establish a dialogue between the university community and the population. Our work has made a research on cultural practices of the student movement in the 1980s. We did an analysis on the process of democratic transition in Brazil, the political participation of youth, their cultural practices in the country, society and politics in the RN, the student movement at UFRN and its cultural practices. We also discussed the concept of culture and cultural practices, but also pointed each of the the main activities and cultural productions organized by students of UFRN in that period. As methodological resource, were used the oral sources, the academic literature on the subject and newspaper pieces, newsletters and advertisement material of the students